2019
DOI: 10.1016/j.envsoft.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

EcoMem: An R package for quantifying ecological memory

Abstract: Ecological processes may exhibit memory to past disturbances affecting the resilience of ecosystems to future disturbance. Understanding the role of ecological memory in shaping ecosystem responses to disturbance under global change is a critical step toward developing effective adaptive management strategies to maintain ecosystem function and biodiversity. We developed EcoMem, an R package for quantifying ecological memory functions using common environmental time series data (continuous, count, proportional)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Accordingly, during the last decade, ecologists have increasingly studied species’ biological traits, and their subset of functional traits, as a way to connect niche‐based mechanisms to community patterns, because it is recognized that species can be grouped according to common effects on ecosystem processes mediated by their functional traits, in addition to common responses to the environment (Cadotte, Arnillas, Livingstone, & Yasui, ; Lavorel & Garnier, ; McGill, Enquist, Weiher, & Westoby, ). Therefore, the assembly processes influencing ecological communities are a result of the combined effects of environmental filters restricting distributions, past and present biotic interactions and stochastic processes (Itter, Vanhatalo, & Finley, ) where the response of the species to these factors will depend on their traits, which in turn are to varying degrees constrained by phylogenetic relationships (Ovaskainen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, during the last decade, ecologists have increasingly studied species’ biological traits, and their subset of functional traits, as a way to connect niche‐based mechanisms to community patterns, because it is recognized that species can be grouped according to common effects on ecosystem processes mediated by their functional traits, in addition to common responses to the environment (Cadotte, Arnillas, Livingstone, & Yasui, ; Lavorel & Garnier, ; McGill, Enquist, Weiher, & Westoby, ). Therefore, the assembly processes influencing ecological communities are a result of the combined effects of environmental filters restricting distributions, past and present biotic interactions and stochastic processes (Itter, Vanhatalo, & Finley, ) where the response of the species to these factors will depend on their traits, which in turn are to varying degrees constrained by phylogenetic relationships (Ovaskainen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature suggests that it might indeed be possible to empirically detect the presence of memory based on the broad properties of a time series. It has been shown that longitudinal time series of microbial communities may carry detectable signatures of underlying ecological processes [4,58]; and recently, Bayesian hierarchical models [10,14], Random Forests [11], neural networks [59], and unsupervised Hebbian learning [60] have been proposed to detect signatures of memory in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that longitudinal time series of microbial communities may carry detectable signatures of underlying ecological processes [7, 70]. Recently, Bayesian hierarchical models [11, 19], random forests [12], neural networks [71], and unsupervised Hebbian learning [24] have been proposed to detect signatures of memory in other contexts. Furthermore, specifically designed longitudinal experiments could be used to characterize memory in real communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ecological context, Ogle et al (2015) and Itter et al (2019) presented a special case of distributed lag models to capture so-called 'ecological memory'. Like distributed lag models, ecological memory models assign a non-negative measure, or weight, to multiple previous time points to capture the possible short-and long-term effects of environmental variables (e.g., climate variables, such as precipitation or temperature) on various environmental processes (e.g., species occupancy).…”
Section: Introductionmentioning
confidence: 99%